Peningkatan Pemahaman Stimulasi Literasi Awal Melalui Pelatihan Multisensori - Rahmatika, Rifa (2016)
The aim of this study was examining the effect of multysensory techniques training to improve mothers understanding about stimulation of literacy for preschool. This training used three methods that are demonstration, discussion and role play. Early literacy stimulation techniques taught in this training include a technique of storytelling, shared book reading, scaffolding and joint writing. The motheds in this study was experimental method with pretest-posttets control group design. The partisipants in this research were 20 mother wich separated in two deferent group. The first grup was experimental group consist of 10 mother with treatment. The second group was control group consist of 10 mother without treatment. The result shows that the multysensory training was improving mothers understading about stimulation fo literacy at preschool. Bandura's social cognitive theory and information processing applied to discuss the result.